2017
DOI: 10.1111/nan.12369
|View full text |Cite
|
Sign up to set email alerts
|

Myopathology in congenital myopathies

Abstract: Congenital myopathies are clinically and genetically a heterogeneous group of early onset neuromuscular disorders, characterized by hypotonia and muscle weakness. Clinical severity and age of onset are variable. Many patients are severely affected at birth while others have a milder, moderately progressive or nonprogressive phenotype. Respiratory weakness is a major clinical aspect that requires regular monitoring. Causative mutations in several genes have been identified that are inherited in a dominant, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 114 publications
1
54
0
2
Order By: Relevance
“…34,[137][138][139][140][141] Mutations in DES, DNAJB6, LMNA, MYOT, PLEC, and TTN give rise to MFMs of various clinical phenotypes and to LGMD without myofibrillar pathology on muscle biopsy (see Table 2). Mutations in genes encoding for other Z-disk-related proteins, such as ACTA1, FHL1, and NEB, in addition to MFM, can also cause congenital myopathies with different histopathologic features, 142,143 whereas mutations in FHL1 and LMNA can also underlie an EDMD phenotype. 66 Mutations in PLEC, another Z-disk-interacting protein, may lead to LGMD2 without skin lesions (LGMD2Q) or epidermolysis bullosa simplex with associated congenital myasthenic syndrome, muscular dystrophy, or pyloric atresia.…”
Section: Muscular Dystrophies With Defective Membranementioning
confidence: 99%
“…34,[137][138][139][140][141] Mutations in DES, DNAJB6, LMNA, MYOT, PLEC, and TTN give rise to MFMs of various clinical phenotypes and to LGMD without myofibrillar pathology on muscle biopsy (see Table 2). Mutations in genes encoding for other Z-disk-related proteins, such as ACTA1, FHL1, and NEB, in addition to MFM, can also cause congenital myopathies with different histopathologic features, 142,143 whereas mutations in FHL1 and LMNA can also underlie an EDMD phenotype. 66 Mutations in PLEC, another Z-disk-interacting protein, may lead to LGMD2 without skin lesions (LGMD2Q) or epidermolysis bullosa simplex with associated congenital myasthenic syndrome, muscular dystrophy, or pyloric atresia.…”
Section: Muscular Dystrophies With Defective Membranementioning
confidence: 99%
“…44 Muscle biopsies normally show numerous rods, but other pathological features have also been described. 45 Data on in vivo muscle function in NEM3 are scarce. Magnetic resonance imaging of muscles of 4 NEM3 patients showed that both lower and upper leg muscles (including the vastus lateralis muscle, from which the majority of the studied biopsies were obtained) had diffuse abnormalities, including fatty replacement of muscle tissue and smaller muscle cross-sectional area.…”
Section: Sarcomere Dysfunction In Nem3 Patientsmentioning
confidence: 99%
“…Nemaline rods are not specific to nemaline myopathy, can be seen in normal myotendinous junction, extraocular muscles and aging muscle and as a minor occurrence in several other myopathies. 10 Infantile onset myopathy was excluded as our patient did not have dilated cardiomyopathy or arthrogryposis, adult onset myopathy was excluded according to the age group. For, HIV rod myopathy, the mother was negative for HIV serology.…”
Section: Discussionmentioning
confidence: 99%